WORD FORMATION OF â€œSTONKS MEMESâ€ ON THE INTERNET - Sobarna, Kaka Ary; Hannan, Abdul (Universitas Islam Negeri Sunan Gunung Djati, 2022)
The word formation process is concerned with how new words are produced, whether through the modification of preexisting terms or through total invention, which later becomes a component of the